Pharmacotherapy in the cardiac catheterization laboratory: evolution and recent developments - Thind GS; Parida R; Gupta N (Dove Medical Press, 2014)
Guramrinder S Thind,1 Raunak Parida,1 Nishant Gupta2 1SDM College of Medical Sciences and Hospital, Dharwad, Karnataka, India; 2University of Texas at Houston, Houston, TX, USAAbstract: Many recent innovations have been made in developing new antiplatelet and anticoagulant drugs in the last few years, with a total of nine new antithrombotic drugs approved by the Food and Drug Administration after the year 2000. This has revolutionized the medical therapy given to manage acute coronary syndrome and support cardiac catheterization. The concept of dual antiplatelet therapy has been emphasized, and clopidogrel has emerged as the most-popular second antiplatelet drug after aspirin. Newer P2Y12 inhibitors like prasugrel and ticagrelor have been extensively studied and compared to clopidogrel. The role of glycoprotein (Gp) IIb/IIIa inhibitors is being redefined. Other alternatives to unfractionated heparin have become available, of which enoxaparin and bivalirudin have been studied the most. Apart from these, many more drugs with novel therapeutic targets are being studied and are currently under development. In this review, current evidence on these drugs is presented and analyzed in a way that would facilitate decision making for the clinician. For this analysis, various high-impact clinical trials, pharmacological studies, meta-analyses, and reviews were accessed through the MEDLINE database. Adopting a unique interdisciplinary approach, an attempt has been made to integrate pharmacological and clinical evidence to better understand and appreciate the pros and cons of each of these classes of drugs. Keywords: acute coronary syndrome, anticoagulants, antiplatelets, percutaneous coronary intervention